Dual Labor Market - Andrzej Klimczuk; Magdalena Klimczuk-Kochańska (The Wiley-Blackwell Encyclopedia of Gender and Sexuality Studies, 2016)
The dual labor market theory is one of the primary explanations for the gender differences in earnings. It shows that gender inequality and stereotypes lead to employment of men and women in different segments of the labor market characterized by various incomes. This theory is based on the hypothesis that such markets are divided into segments, which are divided by different rules of conduct for workers and employers. Differences also include production conditions, terms of employment, productivity of employees, and the characteristics of the workers' jobs. This labor division is related to employee characteristics such as gender, age, and race that define their work environment and lifestyle.
Keywords: J16; J21; 330; employment; gender division of labor; labor; labour market; work